The Metabolic and Hepatic Impact of Two Personalized Dietary Strategies in Subjects with Obesity and Nonalcoholic Fatty Liver Disease: The Fatty Liver in Obesity (FLiO) Randomized Controlled Trial - Marin-Alejandre, Bertha Araceli; Abete, Itziar; Cantero, Irene; Monreal, J. Ignacio; Elorz, Mariana; Herrero, José Ignacio; Benito-Boillos, Alberto; Quiroga, Jorge; Martinez-Echeverria, Ana; Uriz-Otano, Juan Isidro; Huarte-Muniesa, María Pilar; Tur, Josep A.; et al. (Nutrients, 2019)
The prevalence of nonalcoholic fatty liver disease (NAFLD) is increasing worldwide. NAFLD management is mainly focused on weight loss, but the optimal characteristics of the diet demand further investigation. This study aims to evaluate the effects of two personalized energy-restricted diets on the liver status in overweight or obese subjects with NAFLD after a 6 months follow-up. Ninety-eight individuals from the Fatty Liver in Obesity (FLiO) study were randomized into two groups and followed different energy-restricted diets. Subjects were evaluated at baseline and after 6 months. Diet, anthropometry, body composition, and biochemical parameters were evaluated. Liver assessment included ultrasonography, Magnetic Resonance Imaging, elastography, and determination of transaminases. Both dietary groups significantly improved their metabolic and hepatic markers after the intervention, with no significant differences between them. Multivariate regression models evidenced a relationship between weight loss, adherence to the Mediterranean Diet (MedDiet), and a decrease in liver fat content, predicting up to 40.9% of its variability after 6 months. Moreover, the antioxidant capacity of the diet was inversely associated with liver fat content. Participants in the group with a higher adherence to the MedDiet showed a greater reduction in body weight, total fat mass, and hepatic fat. These results support the benefit of energy-restricted diets, high adherence to the MedDiet, and high antioxidant capacity of the diet for the management of NAFLD in individuals with overweight or obesity.